2006
DOI: 10.1071/sr04180
|View full text |Cite
|
Sign up to set email alerts
|

Estimating extractable soil moisture content for Australian soils from field measurements

Abstract: The amount of water that can be stored in soil and evaporated or actively used by plants is a key parameter in hydrologic models and is important for crop and pasture production. Often, the active soil moisture store is estimated from laboratory measurements of soil properties. An alternative approach, described in this paper, is to estimate the extractable soil moisture capacity from direct measurements of soil moisture content in the field. A time series of soil moisture values, over the depth of the soil, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 5 publications
4
18
0
Order By: Relevance
“…Results in Fig. 7 indicate that average effective storage is smaller in summer-dominant rainfall catchments and this is supported by independent estimates of McKenzie et al (2003) and Ladson et al (2006) as shown in Fig. 5 of Potter et al (2005).…”
Section: Assessment Of Climate and Storage Control On Evapotranspirationsupporting
confidence: 81%
See 1 more Smart Citation
“…Results in Fig. 7 indicate that average effective storage is smaller in summer-dominant rainfall catchments and this is supported by independent estimates of McKenzie et al (2003) and Ladson et al (2006) as shown in Fig. 5 of Potter et al (2005).…”
Section: Assessment Of Climate and Storage Control On Evapotranspirationsupporting
confidence: 81%
“…No correlation was found for wet catchments (W À /W + < 1.5). Ladson et al (2006) showed that estimate of PAWC using soil data could be considered as lower limit of field-based estimate the actual dynamic soil moisture store, and this finding was confirmed for winterdominant catchments as the magnitudes of average effective storage are the same as those estimated by Ladson et al (2006).…”
Section: Storage Control On Evapotranspirationsupporting
confidence: 64%
“…Hochman et al (2001) developed close relationships between the PAWC of farmers' soils and soil type, crop species, and soil depth, but these parameters required access to extensive soil water data and represented only two main soil classes: the grey and black Vertosols. Ladson et al (2002) used the FARMSCAPE database and other data to compare PAWC estimates with the Atlas of Australian Soils and found significant differences. They concluded both that the field measure of PAWC is essential and that a collated PAWC database was lacking in Australia, in contrast to other soil properties.…”
Section: The Practicalities Of Paddock-specific Simulation For Farmersmentioning
confidence: 99%
“…As the three assumptions needed for the use of Equation are rarely met in complex terrain or even in agricultural areas, general consensus exists that instead of using some form of Equation the TAW is best measured directly in the field (Israelsen and West, ; Ritchie, , b; Ratliff et al ., ; Hillel, ; Romano and Santini, ; Kirkham, ; Ladson et al ., ). However, field measurements in each soil‐vegetation‐geology unit of a watershed would take too much effort and expense even under the best of conditions with stone‐free soils and shallow rooting depths.…”
Section: Case Study Iii: Dpwm In the San Gabriel Mountains Of Californiamentioning
confidence: 54%
“…The third assumption that the effective depth for root water uptake can be determined from field observations in soil pits may apply to agricultural fields with relatively shallow rooting depths but will fail in complex terrain due to the challenges of soil and root sampling at depth, and the difficulty of estimating in situ root activity over the entire root zone (Jackson et al ., ; Feddes et al ., ). In Australia, active soil depths, i.e., rooting depths, for agricultural crops, grass, and fallow based on field measurements of extractable water generally varied between 1 and 2 m, while those of trees are more variable ranging from 1 to 12 m, but active soil depths of 5 m were measured for crops and grass on deep sandy soils (Ladson et al ., ). In eastern Amazonia, water stored at 2‐8 m soil depth contributed more than 75% of water uptake not only in forest but also in degraded pasture with deep‐rooted woody plants during the severe dry season of 1992 (Nepstad et al ., ).…”
Section: Case Study Iii: Dpwm In the San Gabriel Mountains Of Californiamentioning
confidence: 99%